2014
DOI: 10.1007/s00394-014-0736-6
|View full text |Cite
|
Sign up to set email alerts
|

Whey peptide ingestion suppresses body fat accumulation in senescence-accelerated mouse prone 6 (SAMP6)

Abstract: These data suggest that a normal (or moderate excess) dietary density of whey peptide attenuates body fat accumulation via upregulation of fatty acid oxidation in skeletal muscle in aging mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Soybean-derived peptides improved glucose transport and insulin signaling in high fat diet-fed mice and in insulin-resistant C2C12 myotubes via upregulation of insulin receptor and insulin receptor substrate 1 and activation of AMPK [51,52]. Whey peptides were also previously shown to stimulate glucose uptake, glycogen synthesis, and AMPK activity [24,27,29]. Our current work complements these studies by showing that whey peptide treatment ameliorates lipotoxicity-induced insulin-resistance in C2C12 myotubes.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Soybean-derived peptides improved glucose transport and insulin signaling in high fat diet-fed mice and in insulin-resistant C2C12 myotubes via upregulation of insulin receptor and insulin receptor substrate 1 and activation of AMPK [51,52]. Whey peptides were also previously shown to stimulate glucose uptake, glycogen synthesis, and AMPK activity [24,27,29]. Our current work complements these studies by showing that whey peptide treatment ameliorates lipotoxicity-induced insulin-resistance in C2C12 myotubes.…”
Section: Discussionsupporting
confidence: 71%
“…Insulin sensitization of these tissues, therefore, can potentially reduce and prevent systemic insulin resistance and its complications. Recent studies have demonstrated that hydrolysis of milk proteins, including whey proteins, generates bioactive peptides that can affect glucose homeostasis [18,24,29]. However, it remained unclear whether and how whey peptide exposure affects lipid metabolism and insulin sensitivity in adipose tissue and skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been reported that the consumption of whey protein hydrolysate (WPH) is associated with other health effects, such as an increase in the translocation of GLUT-4 (Morato et al, 2013), an improvement in satiety signals (Luhovyy, Akhavan, & Anderson, 2007) and an increase in glycogen content (Morifuji, Sakai, Sanbongi, & Sugiura, 2005). Several molecular effects caused by the consumption of WPH have been connected to the presence of bioactive peptides (Ichinoseki-Sekine, Kakigi, Miura, & Naito, 2014;Luhovyy et al, 2007), including the possible role of branched-chain amino acids (BCAAs) and peptides in the HSP response (De Moura et al, 2014). The presence of BCAA-containing peptides in WPH has been reported (Morifuji, Koga, Kawanaka, & Higuchi, 2009).…”
Section: Introductionmentioning
confidence: 98%